Content is king: Malaysian industry experts point of view on local content for mobile phones - Ariffin Shamsul Arrieya, Dyson Laurel Evelyn, McKenzie Darlene Hoskins, (N/A, 2012)
Content is king: Malaysian industry experts point of view on local content for mobile phones by Ariffin Shamsul Arrieya, Dyson Laurel Evelyn, McKenzie Darlene Hoskins,